PP.22.08: DOPPLER INDEXES OF LEFT VENTRICULAR SYSTOLIC AND DIASTOLIC FLOW AND CENTRAL PULSE PRESSURE IN RELATION TO RENAL RESISTIVE INDEX. (June 2015) - Cauwenberghs, N.; Kuznetsova, T.; Knez, J.; Thijs, L.; Liu, Y.P.; Gu, Y.M.; Staessen, J.A.
Abstract : Objective: The cardio-renal interaction occurs via hemodynamic and humoral factors. Noninvasive assessment of renal hemodynamics is currently possible by assessment of the renal resistive index (RRI) derived from intrarenal Doppler arterial waveforms as (peak systolic velocity - end-diastolic velocity)/peak systolic velocity. Limited information is available regarding the relationship between RRI and cardiac hemodynamics. We investigated these associations in randomly recruited subjects from a general population. Figure. No caption available. Design and method: In 171 participants (48.5% women; mean age, 52.2 years) we measured RRI (mean, 0.60) and left ventricular outflow tract (LVOT) and transmitral (E and A) blood flow peak velocities and its velocity time integrals (VTI) using pulsed wave Doppler. Using carotid applanation tonometry, we measured central pulse pressure and arterial stiffness indexes such as augmentation pressure and carotid–femoral pulse wave velocity. Results: In stepwise regression analysis, RRI independently and significantly increased with female sex, age, body weight, brachial pulse pressure, and use of β-blockers, whereas it decreased with body height and mean arterial pressure. In multivariable-adjusted models with central pulse pressure and arterial stiffness indexes as the explanatory variables, we observed a significant and positive correlation of RRI only with central pulse pressure (P < 0.0001). Among the Doppler indexes of left ventricular blood flow, RRI was significantly and positively associated with LVOT and E peak velocities (P < 0.012) and VTIs (P < 0.010). Conclusions: We demonstrated that, in unselected subjects, RRI was significantly associated with central pulse pressure and left ventricular systolic and diastolic Doppler blood flow indexes. Our findings imply that in addition to the anthropometric characteristics, cardiac hemodynamic factors influence the intrarenal arterial Doppler waveform patterns.